Effect of Dietary Fiber Intake on Intestinal Motility in Healthy Adults. A Clinical Study - AHUJA, NEHA; ABRO, MUJEEB UR REHMAN; MUJEEB, SHAISTA; WADHWA, MAHESH KUMAR (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Normal intestinal motility plays a critical role in normal digestion and clearance. Dietary fiber plays a role in the regulation of the bowel activity though majority of the adult population in the adult population is consuming inadequate amounts. This study investigated the impact of the consumption of dietary fibers on the bowel movement of healthy adults. Methods: The cross-sectional study was conducted on 100 healthy adults aged adults of 18 to 60 years. Dietary fiber was assessed using a validated food frequency questionnaire and categorized into low (<15 g/day), adequate (15 25 g/day), and high (> 25 g/day). Intestinal motility was measured by use of frequency of bowel motion and Bristol Stool Form Scale. Data were analyzed using chi-square and ANOVA. Results: The excessive consumption of fiber had a tremendous improvement in the intestinal motility with 85 percent of the participants reporting favorable bowel frequency and 80 percent with favorable stool consistency. Conversely, the low-fiber consumers reported more infrequent rates of the bowel movement (52.9%), hard stool rates (58.8%). The statistical result indicated that there existed significant association between the intake of fiber and the bowel frequency (p = 0.001) and the stool consistency (p = 0.002). Conclusion: There is a close relationship between improved intestinal motility of healthy adults and increased dietary fiber intake. The massive consumption of fiber may become an encouraging intervention so that to maintain the bowel functions normal and secure the avoidance of the gastrointestinal issues.